Socially anxious mothers' narratives to their children and their relation to child representations and adjustment. (25th November 2014) - Murray, Lynne; Pella, Jeff E.; De Pascalis, Leonardo; Arteche, Adriane; Pass, Laura; Percy, Ray; Creswell, Catharine; Cooper, Peter J.
Abstract: Anxious mothers' parenting, particularly transfer of threat information, has been considered important in their children's risk for social anxiety disorder (SAnxD), and maternal narratives concerning potential social threat could elucidate this contribution. Maternal narratives to their preschool 4- to 5-year-old children, via a picture book about starting school, were assessed in socially anxious ( N = 73), and nonanxious ( N = 63) mothers. Child representations of school were assessed via doll play (DP). After one school term, mothers (Child Behavior Checklist [CBCL]) and teachers (Teacher Report Form) reported on child internalizing problems, and child SAnxD was assessed via maternal interview. Relations between these variables, infant behavioral inhibition, and attachment, were examined. Socially anxious mothers showed more negative (higher threat attribution) and less supportive (lower encouragement) narratives than controls, and their children's DP representations SAnxD and CBCL scores were more adverse. High narrative threat predicted child SAnxD; lower encouragement predicted negative child CBCL scores and, particularly for behaviorally inhibited children, Teacher Report Form scores and DP representations. In securely attached children, CBCL scores and risk for SAnxD were affected by maternal anxiety and threat attributions, respectively. Low encouragement mediated the effects of maternal anxiety on child DP representations and CBCL scores. Maternal narratives are affected by social anxiety and contribute to adverse child outcome.